A study of the theory and practice of instructional leadership among post-primary principals and deputy principals in Ireland - Swan, Patricia Verity (Trinity College (Dublin, Ireland). School of Education, 2010)
The research commenced with two exploratory studies (2001/2002) in Ireland and Texas into teacher employment patterns (teacher recruitment, teacher turnover and retention) at post-primary level in both Ireland and Texas. Principals were asked the question “Why do teachers stay in teaching?" The Texan principals claimed that they could and did make a positive difference in the experience of a teacher through instructional leadership, in marked contrast to the responses of the Irish principals to the questions on leadership who saw their role as mainly managerial / administrative. This led to an investigation of the effect of culture on teaching, which provided further information on principals' leadership, following the statement by the National Association of Principals and Deputy Principals (NAPD) 2005 that instructional leadership was the way forward in Ireland, the study focused on the nature of instructional leadership, its theory and practice.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin